THE EFFECT OF MAGNESIUM DRUGS ON THE PHYSICAL PERFORMANCE OF YOUNG PEOPLE WITH MITRAL VALVE PROLAPSE: RESULTS OF NONCOMPARATIVE STUDY - K. M. Dzeranova; A. G. Avtandilov; N. V. Vertkina (Рациональная фармакотерапия в кардиологии)
Aim. To study the dynamics of physical performance in young people with mitral valve prolapse (MVP) while taking magnesium orotate. Material and methods. Patients with MVP and phenotypic characteristics of undifferentiated connective tissue dysplasia (n=54, aged 19.2±0.3 years) were included into the study. Hemodynamic parameters of physical performance were evaluated before and after taking magnesium orotate for 8 weeks. Results. Improvement of physical performance was found after magnesium orotate taking: threshold double product elevated from 1.86±0.05 to 2.06±0.05 units (p<0.001); threshold power increased - relative physical performance raised from 1.35±0.04 W/kg to 1.44±0.04 W/kg (p<0.05) and specific work from 12.3±0.65 W/kg to 14.2±0.71 W/kg (p<0.001); recovery time decreased. Conclusion. Improvement of hemodynamic maintenance of exercise load was found in adolescents with MVP during magnesium orotate taking. It was accompanied with physical performance and threshold power elevation and recovery time reduction.